The principal’s transformational leadership as a variable related to the organisational climate in educative institutions from a district of Lima - Cervera Cajo, Luz Emérita (2021)
The current research work had as main purpose to establish the link between the variable’s transformational leadership and organisational climate in teachers from different public institutions from a district of Metropolitan Lima. This research has a quantitative focus and uses a non-experimental design of a correlational scope. The type of sample is probabilistic and is composed by 171 teachers, which are distributed between five public educative institutions from a district of Lima. Two instruments of evaluation, previously validated, were applied to this sample: The Inventory of Transformational Leadership elaborated by Antuanet Chirinos (2010) and the Inventory of Organisational Climate of Rubén Soria (2010). The data obtained were processed using the statistical package SPSS version 25, which results confirm the principal hypothesis, given that the studied variables are correlated among them (r = 0,85). Furthermore, the results allow to stablish that the dimensions of the two variables are significantly correlated.